Large–scale genetic analysis and biological traits of two SigB factors in Listeria monocytogenes: lineage correlations and differential functions - Mao, Pan; Wang, Yan; Gan, Lin; Liu, Lingyun; Chen, Jinni; Li, Lingling; Sun, Hui; Luo, Xia; Ye, Changyun (Frontiers in Microbiology, 2023)
Listeria monocytogenes is globally distributed bacterium that exhibits genetic diversity and trait heterogeneity. The alternative sigma factor SigB serves as a crucial transcriptional regulator essential for responding to environmental stress condition and facilitating host infection. Here, we employed a comprehensive genetic analysis of SigB in a dataset comprising 46921 L. monocytogenes genomes. Our study revealed the presence of two predominant SigB factors (SigBT1 and SigBT2) in L. monocytogenes with a robust correlation between SigBT1 and lineage I and III, as well as SigBT2 and lineage II. Comparing the functional attributes of SigBT1 and SigBT2, the results showed revealed that SigBT1 exhibits a superior performance in promoting cellular invasion and cytotoxicity, as well as enhanced abilities in biofilm formation and cold tolerance under minimally defined media conditions, compared to SigBT2. The functional characteristics of SigBT1 suggests a potential association with the epidemiology of lineage I and III in both human hosts and the natural environment. Our findings highlight the important role of distinct SigB factors in influencing the biological traits of L. monocytogenes lineages, thus underscoring its distinct pathogenic and adaptive attributes.